Rice Terrace Experience in Japan: An Ode to the Beauty of Seasonality and Nostalgia - Qian Wang; Xiaoqi Yang; Xinyu Liu; Katsunori Furuya (Land, 2024)
Rice terraces are a time-honored agricultural feature that overcomes rough terrain and hostile growing conditions. In addition to playing an essential role in agricultural production and land conservation, rice terraces have been recognized as living cultural landscapes, important agricultural heritage, and popular agritourism destinations for their aesthetic, sociocultural, and environmental values. However, there is a lack of understanding of this emerging niche market, especially from outsider perspectives. To fill the gap, this study analyzes Google Maps reviews of seventy representative rice terraces in Japan based on a mixed-method content analysis, aiming to identify visitors’ overall experiences, seasonal perceptions, and the causes of negative experiences. The results indicate that the overall experience of rice terraces in Japan includes seven themes: agricultural landscapes, times and seasons, visual perception, accessibility and infrastructure, sense of place, Genfukei of Japan, and food. Visitors’ perceptions toward the four seasons of the rice terraces have distinctive characteristics and result in different satisfaction levels. The main reasons for negative experiences are farmland abandonment, lack of character, poor accessibility, and bad timing. Leveraging the power of netnography, the study sheds light on the sustainable development of agricultural heritage tourism through the introduction of rice terrace conservation initiatives in Japan and the exploration of rice terrace experience.